2012
DOI: 10.1016/j.jvs.2011.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Carotid endarterectomy in the acute phase of stroke-in-evolution is safe and effective in selected patients

Abstract: This short series demonstrates that CEA in the acute phase of SIE with strict selection criteria and close blood pressure monitoring is safe, even after recent thrombolytic therapy, and is effective in functional outcome at 3 months. Larger series of patients are required to confirm the safety and efficacy of this management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 31 publications
2
25
0
2
Order By: Relevance
“…The absence of complications in Group A could be explained by the accurate selection of patients. However, Lesèche et al 2012; reported excellent outcomes of early CR performed in the acute phase of stroke in evolution, [13] a population with a higher risk pro ile that was excluded from Group A in our study. This could also explain our good results for this group.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The absence of complications in Group A could be explained by the accurate selection of patients. However, Lesèche et al 2012; reported excellent outcomes of early CR performed in the acute phase of stroke in evolution, [13] a population with a higher risk pro ile that was excluded from Group A in our study. This could also explain our good results for this group.…”
Section: Discussionmentioning
confidence: 63%
“…Nevertheless, several small monocentric studies reported favourable outcomes, including patients with major strokes during acute phase [15,17,18]. Lesèche et al 2012; reported no death or postoperative stroke for 27 patients who underwent CR during the acute phase of stroke with a median delay of six days from symptom onset to surgery [13]. Results of these studies tend to consider a prompt surgical approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients who have received stroke thrombolysis, four small case series suggest that early carotid endarterectomy can still be performed safely. [34][35][36][37] Who benefits most from endarterectomy?…”
Section: Normal Variants Such As Kinked Carotidsmentioning
confidence: 99%
“…Despite these limitations, we were able to show that during hospitalization (mean, 10 days) of patients who underwent CR, it was possible to carry out stroke management, stroke care and CR procedures, including post‐intervention monitoring with at least 1 day in a stroke unit or intermediate care (patients usually stayed in hospital for 3 days after CR, regardless whether CEA or CAS was performed). Two other studies have recently investigated the safety of performing CEA within a median time of 5 days in patients with crescendo TIA, and within 6 days in patients with stroke‐in‐evolution .…”
Section: Discussionmentioning
confidence: 99%